Purificação e caracterização bioquímica de BthMP: uma nova metaloprotenaise do veneno de Botrops moojeni (Caiçaca) - Gomes, Mário Sérgio Rocha (2006)
In this work a new metalloproteinase (BthMP) was purified from the snake venom of Bothrops moojeni. This enzyme was homogeneous by native and SDSPAGE it showed polypeptide chain of 23,5 kDa, pI = 7,1 and N-terminal blocked. BthMP is comprised of high proteolytic activity on casein, fibrin and bovine fibrinogen, but no coagulating, esterase, phospholipase A2 activities, and lightly hemorrhagic; it was inhibited by EDTA, EGTA and 1,10-phenanthroline and maintained its activity on pH of 7,0 at 9,0 and temperature of 5 to 40°C. Assays with metal ions showed that Ca++ is an activator, whereas Zn++ and Hg++ inhibited about 50 and 80%, respectively. The edema evidenced the important role of the toxin in the inflamatory activity of the venom. BthMP also caused uncloting, and provoked histological alterations in gastrocnemius muscle of mice inducing hemorrhage, necrosis and leucocytic infiltrate. The molecular mass and the inhibition assays suggest that the metalloproteinase BthMP belongs to class P-I SVMPs.